(untitled) (Research, Society and Development, 2021)
Illegal wildlife trade is a problem with ecological and social repercussions. In addition to causing the decline of several natural populations, this practice has direct consequences over the captured individuals, such as immunosuppression conditions that can result in the manifestation of various pathogens. In Brazil, wild bird trafficking stands out as one of the most popular forms of this practice. The most sought-after species usually have aesthetic or sound appeals, like many Passerine species. The Northeastern Cardinal (Paroaria dominicana) is one of these species, considered one of the most trafficked in the country. In this work, we analyzed 26 specimens of Paroaria dominicana from a rescue action carried out by IBAMA. Necropsy and spontaneous sedimentation techniques were performed to check the presence of helminths and eggs in the organs of the specimens analyzed, as well as weighing and measuring of the cadavers. We found the presence of nematode species in 05 specimens; all belonging to the genus Diplotriaena, including the species Diplotriaena delirae, registered for the first time in the Paroaria dominicana helminth fauna. We observed the presence of eggs characteristic of the genus Diplotriaena and Heterakis, the latter also unprecedented in the helminth fauna of Paroaria dominicana until the present work. The presence of new species in the helminth fauna of Paroaria dominicana may be associated with direct contact with other wild species during capture and illegal transport, as well as the sanitary conditions associated with these stages of bird trafficking.